2003
DOI: 10.1162/154247603322391170
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms and Welfare State Dynamics

Abstract: The paper analyses the interaction between economic incentives and work norms in the context of social insurance. If the work norm is endogenous in the sense that it is weaker when the population share of beneficiaries is higher, then voters will choose less generous benefits than otherwise. We also discuss welfare‐state dynamics when there is a time lag in the adjustment of the norm in response to changes in this population share, and show how a temporary shift in the unemployment rate may cause persistence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 3 publications
(5 reference statements)
0
56
0
Order By: Relevance
“…The high and volatile work absence due to sickness observed in several countries during the last decades has spurred researchers to discuss the importance of norms and social interactions in this context (Lindbeck and Persson, 2010;Lindbeck and Nyberg, 2006;Lindbeck, Nyberg and Weibull, 2003;Ichino and Maggi, 2000). Several studies have…”
Section: Introductionmentioning
confidence: 99%
“…The high and volatile work absence due to sickness observed in several countries during the last decades has spurred researchers to discuss the importance of norms and social interactions in this context (Lindbeck and Persson, 2010;Lindbeck and Nyberg, 2006;Lindbeck, Nyberg and Weibull, 2003;Ichino and Maggi, 2000). Several studies have…”
Section: Introductionmentioning
confidence: 99%
“…Besley and Coate (1992a), for example, assumed that the utility of being on welfare is reduced by some function of the fraction of the population that is not truly needy and is instead reducing labor supply to go onto welfare. Lindbeck et al (1999) simply assumed that the utility of being on welfare is reduced by the number of others who are on welfare, but went on to analyze the voting equilibria that would set benefit levels that would generate different welfare caseloads as an equilibrium outcome. In a somewhat different vein, Nechbya (1999) assumed that the stigma of having nonmarital births (which is a condition for welfare eligibility) is reduced by the magnitude of the aggregate nonmarital birth rate, and then showed that a change in welfare benefits can initiate a nontrivial change in that birth rate through multiplier effects.…”
mentioning
confidence: 99%
“…For a different explanation of why a generous social safety net may induce persistence pointing to the role of work norms, see e.g. Lindbeck (1995) and Lindbeck et al (2003). If there is a strong norm to be self-supporting, employment may be high, even if economic incentives to work are small due to generous welfare schemes.…”
Section: Business Cycle Dependent Unemployment Insurancementioning
confidence: 99%